Effect of Pakistani bentonite on properties of mortar and concrete - Ahmad, S.; Barbhuiya, Salim; Elahi, A.; Iqbal, J. (2011)
Bentonite is composed primarily of montmorillonite and is useful in a wide range of applications. This paper presents the results of an experimental investigation carried out to evaluate the possibility of using a Pakistani bentonite (from Jehangira, Swabi District) as a cement replacement material in mortar and concrete. The cement in mortar and concrete was replaced with the bentonite at 0%, 20%, 30%, 40% and 50% by cement mass. The strength activity index of bentonite was determined 'as received' (20°C) and 'heated' (treatment at 500°C and 900°C). The test results indicated that the strength activity index of bentonite conformed to the ASTM Standard C618 specifications, except for the '900°C heated' bentonite. The water absorption decreased for mortar containing up to 30% bentonite and then steadily increased at higher bentonite loadings. When immersed in 5% Na 2SO4 and 2% MgSO4 solution, the greatest compressive strength was observed for mortar containing 30% bentonite. The water demand of concrete increased with increasing bentonite content. Although the compressive strength of concrete decreased progressively as the substitution level of bentonite was increased, the compressive strength of concrete containing 30% 'as received' bentonite was found to be 70% of the control concrete, whereas for concrete containing 30% '500°C heated' bentonite, the strength was found to be 79% of the control concrete. It can be concluded that this Pakistani bentonite can be used to replace up to 30% of cement to produce concrete with sufficient compressive strength for low-cost construction resistant to sulphate attack. © 2011 Mineralogical Society.